Giant radicular cyst with bilateral maxillary sinus involvement - Emre Kose; Emin Murat Canger; Yildiray Sisman; Fatma Gulfesan Yildirim Canakci; Gulsah Cubukcu; Hulya Akgun (Wolters Kluwer Medknow Publications, 2014)
Radicular cysts are the most common cysts of the jaws. They are localized on the apex of the teeth with necrotic pulp. They are classified as inflammatory cysts. Radiographically, they appear as an oval radiolucent lesion with well-defined radiopaque border. They develop slowly, and asymptomatic unless infected. Because of this they can reach big dimensions. Intraoral examination of an 21-year-old man revealed a fluctant swelling on the palatinal and vestibular mucosa of the incisor-canine region. Radiographic examination revealed well defined and uniformly radiolucent lesion present between the left and right molar regions. The lesion was extending to nasal cavity and left and right maxillary sinus regions. The result of the histopathological examination was reported as radicular cyst. In this report it was aimed to present a giant radicular cyst case.